2010
DOI: 10.1073/pnas.0911691107
|View full text |Cite
|
Sign up to set email alerts
|

Principles of conduction and hydrophobic gating in K + channels

Abstract: We present the first atomic-resolution observations of permeation and gating in a K þ channel, based on molecular dynamics simulations of the Kv1.2 pore domain. Analysis of hundreds of simulated permeation events revealed a detailed conduction mechanism, resembling the Hodgkin-Keynes "knock-on" model, in which translocation of two selectivity filter-bound ions is driven by a third ion; formation of this knock-on intermediate is rate determining. In addition, at reverse or zero voltages, we observed pore closur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

41
367
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(417 citation statements)
references
References 58 publications
41
367
6
Order By: Relevance
“…Interestingly, the studies in some Kv channels suggest that the intrinsically most stable state of the Kv pore is the closed state [1,52,53]. The VSDs thus do not need to actively push the S4-S5 linker down to close the pore because the pore cavity is highly hydrophobic [52]. Consistently, a molecular simulation further showed that the limited motion of a single VSD towards the resting state is sufficient to close the pore [1].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Interestingly, the studies in some Kv channels suggest that the intrinsically most stable state of the Kv pore is the closed state [1,52,53]. The VSDs thus do not need to actively push the S4-S5 linker down to close the pore because the pore cavity is highly hydrophobic [52]. Consistently, a molecular simulation further showed that the limited motion of a single VSD towards the resting state is sufficient to close the pore [1].…”
Section: Discussionsupporting
confidence: 54%
“…Some previous studies supported that the Kv pore is intrinsically more stable when closed, which distinguishes it from constitutively open K2P channels [52,53]. Notably, the study on KvLm channels revealed that pore only module can populate at open state, suggesting that the pore of Kv channels may also reside in between closed-activated and open state [16].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Among these studies, the "knock-on" mechanism still dominates as an explanatory account of the permeation processes (Bernèche and Roux, 2001;Jensen et al, 2010). One may define the knock-on mechanism as an electrostatic repulsion taking place among the ions permeating in and out of the pore in a manner that drives ion flux efficiently (Hille, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, computer simulations have suggested other arrays of ions and water molecules in the selectivity filter (Khalili-Araghi et al, 2006;Furini and Domene, 2009;Jensen et al, 2010;Nelson, 2011). Two issues were raised: may ions be located adjacently, and whether there are five sites rather than four sites in the selectivity filter.…”
Section: Discussionmentioning
confidence: 99%